Metric system education in J. Damijonaitis manuals - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2003)
Metric system education in J. Damijonaitis manuals is presented. Basic actions with metrical number are discribed.